The Effect of Using Financial Information Service System (SLIK) on Bad Credit Rate in Fintech Peer to Peer Lending - Elida Tobing (Ridwan Institute, 2023)
The development of Fintech Peer to Peer Lending (P2P Lending) in Indonesia is very rapid in supporting increased financial inclusion. Along with the increase in the value of loans disbursed through P2P Lending, the ratio of bad loans or what is often referred to as Non Performing Loans (NPL) also continues to increase. Literature review article